Partisipasi Politik Masyarakat Tionghoa dalam Pemilihan Kepala Daerah - Agung Suharyanto (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2014)
This study aims to determine how the Chinese Peoples Political Participation and the constraints faced by the Chinese community in Binjai city elections in 2010 in Kampung Tanjung District of Binjai City. The methodology used in this research is descriptive qualitative method is a way or method of describing the state of research in the field or object. Total population in this study were all heads of families Kampung Tanjung Binjai City District of the ethnic Chinese as many as 326 households. The sampling technique is by means of random sampling of 10% of the population. Then the sample in this study is 10% of the 326 households 32 households of ethnic Chinese are drawn randomly. Data collection techniques used were observation, questionnaires, and interviews. The data obtained in the study were analyzed using descriptive analysis method, then analyzed using frequency tables. Based on the analysis of observation, questionnaires and interviews were then held a discussion on the research results obtained the conclusion that the Chinese community in Kampung Tanjung District of Binjai City has participated in the elections of Binjai in 2010. Thus it is clear these results support the hypothesis, which also means that the hypothesis acceptable.